The association of oxidant–antioxidant status in patients with chronic renal failure. (2nd January 2016) - Aziz, Manal A.; Majeed, Ghanim H.; Diab, Kareem S.; Al-Tamimi, Raid J.
Abstract: Oxidative stress has been linked to disease progression, including chronic renal failure (CRF). The aim of the present study was to determine malondialdehyde (MDA) as a sign of lipid peroxidation, and to investigate the association between antioxidant activities and three trace elements, in 49 patients with CRF. The erythrocyte and plasma trace elements [selenium (Se), zinc (Zn), and copper (Cu)] and antioxidant defense levels were determined: glutathione peroxidase (GPx), superoxide dismutase (SOD), catalase (CAT), vitamins E and C. The obtained values were compared with 42 age- and sex-matched healthy controls. There were significantly lower mean values of plasma Se, GPx, vitamins E and C, erythrocyte Se, SOD and CAT levels in the patient group compared to the control group ( p < 0.001). Plasma MDA showed a significant increase in all CRF patients in comparison with controls. No significant difference was found in plasma Cu, Zn, and erythrocyte GPx, Cu and Zn levels between patient and control groups. These findings indicate oxidative stress is present in patients of CRF, and may serve to establish a simple protocol for evaluation of renal function.